Bancassurance Business In India: Reviews From The Perception of Bank Employees - Kaur, Navdeep; Kaur, Ravneet (Gyan Management Journal, 2024)
Over the past one decade, financial market of India has witnessed a remarkable change in banking and insurance sector. The insurance company sells insurance related products with the help of bank sales channel. When these two big financial institutions join together with a mutual purpose, it gives birth to “Bancassurance”. The success of bancassurance business hinges on the employees’ attitude who executes bancassurance practices in banks. The purpose of the study is to provide better insights of the employees’ perspective on bancassurance. The study reviewed various research papers taken from relevant research databases. Further, study explains the analysis of employee’s perspective under three dimensions i.e. motivating factors of bancassurance, perceived benefits of bancassurance and problems of bancassurance. The results of the study revealed that positive perception of employees plays a vital role in success of bancassurance and enhances the excellent customer’s relationship.